Improving Discipline and Responsibility of Student Learning Through Project Assessment - Sitti Mania (Al-Ulum, 2015)
This ‘classroom action research’ aims to determine the effectiveness of the project assessment at Islamic Junior School (Madrasah Tsanawiyah) Model Makassar in the VIII/a class as subject research. The study carried out in two cycles, data collection was done by employing three ways: questionnaires, observation and test administration. The result showed that the project assessment was able to improve: 1) student discipline, shown on average 73,78% of the first cycle and the second cycle was 91,72%. 2) Responsibility for student learning, the average seen in the first cycle of 66,37% and 85,77% for the second cycle. 3) Student learning outcomes, the first cycle were 51,72% while in the second cycle there was 17,24% score below the minimum completeness criteria. On the individual test conducted at the end of the second cycle showed that there are only 4 students (13,79%) who had not reached the minimum completeness criteria.